Implementation of Audio-Visual Teaching Media in Improving Students’ Listening Comprehension: A Case on Teaching Method - Kartika, Dewi; Siahaan, Sanggam; Herman, Herman; Rumapea, Elina Lulu; Silalahi, Tiodora Fermiska (Journal of English Language and Education, 2023)
The objective of this study was to determine the effect of audio-visual media on listening comprehension of eleventh grade students of SMA Negeri 5 Pematang Siantar on narrative text. This study used an quantitative research with quasi-experimental design with a sample of 72 eleventh grade students of SMA Negeri 5 Pematang Siantar selected by purposive sampling. The experimental group was given material using audio-visual teaching media, while the control group was given material with lecture-based learning traditional teaching method. The data were analysed using the t test. From the results of data analysis, the mean pre-test and post-test values for the experimental class were 40 and 90, while for the control class were 50.1, and 78. It is also known that the average value in experimental class reached 90 and control class 78. The results showed that students who learned by using audio visual media had better listening comprehension than students who learned with lecture-based learning traditional teaching method.  Hypothesis testing also shows that audio visual teaching has a significant effect on listening comprehension on a narrative text. The results show that T-test is higher than T-table (4.121.667) with the level of significance 5%, then Ha is accepted and H0 is rejected. Based on the results of the research, it can be concluded that the use of audio-visual media affected students' listening comprehension on narrative text.